Non-standard Emotions and Aesthetic Understanding - Irene Martínez Marín (Estetika, 2020)
Winner of the Fabian Dorsch ESA Essay Prize. For cognitivist accounts of aesthetic appreciation, appreciation requires an agent (1) to perceptually respond to the relevant aesthetic features of an object o on good evidential grounds, (2) to have an autonomous grasp of the reasons that make the claim about the aesthetic features of o true by pointing out the connection between non-aesthetic features and the aesthetic features of o, (3) to be able to provide an explanation of why those features contribute to the overall aesthetic value of o. In this framework, aesthetic emotions have traditionally been confined to the level of aesthetic perception (1) and dismissed from the process of reason-giving (2, 3). I argue that this dismissal is due, firstly, to a questionable perceptual reading of the connection between emotional experience and value, and, secondly, to a narrow focus on the basic emotions. My argument will reveal that the non-standard or ‘intellectual’ emotions, the emotions which are in fact most important to appreciation, can play a significant epistemic role in our appreciative practices. They can do this because they (a) help us to deliberately focus our attention and (b) place the appreciator in a state of second-order awareness of their mental states. I conclude the paper by showing how these two epistemic tools (a, b) can help the appreciator to meet the explanatory/justificatory conditions (2) and (3).